USV/UUV Cooperative Navigation Algorithm Based on Moving Long Baseline and Navigation Error Correction - Huifeng JIAO; Chen YE; Wenchu WANG; Zhaoyong MAO; Yintao WANG (水下无人系统学报)
Unmanned undersea vehicles(UUVs) undergo a cumulative increase of inertial navigation error caused by long-term cooperative movement. In order to reduce the relative navigation errors between unmanned surface vessels(USVs) and UUVs and improve the navigation accuracy of UUVs, a USV/UUV cooperative navigation algorithm based on moving long baseline and navigation error correction was proposed in this paper. The algorithm was based on underwater acoustic communication ranging. First, UUV collected the relative distance information between it and USVs, calculated the relative navigation error correction, and then added the correction to the current navigation position of USVs. Finally, the accumulated inertial navigation error of UUVs was corrected by combining the formation setting between USVs and UUVs and the position calculated by the UUVs’ low-precision navigation equipment. The simulation results show that the navigation accuracy of UUVs can be significantly improved during the USV/UUV cooperative movement by blending the corrected UUV position information with the position calculated by the inertial navigation of UUV.